The Influence of Leadership Behavior, Work Environment, Compensation on Employee Work Outcomes - Budi Siregar; Dewi Suma (Jurnal Mantik, 2022)
This study examines the relationship between leadership behavior, work environment, and compensation to motivation and the relationship between motivation and work productivity of employees. Data collection was carried out by interviewing and distributing questionnaires to employees at PT. Sinar Pantja Daja, Central Java Province, Indonesia. The Central Java region in Indonesia is known as an industrial area. The sampling technique was carried out purposively based on specific criteria. Data analysis using Structural Equation Modeling (SEM). This research review provides practical recommendations and strategic policies in managing and increasing employee productivity. The results showed that motivation has an essential role as a mediator in increasing employee productivity. Research respondents numbered 232 employees, limited to one work department to not represent the entire population.